2010
DOI: 10.4049/jimmunol.1001550
|View full text |Cite
|
Sign up to set email alerts
|

Discrete TCR Repertoires and CDR3 Features Distinguish Effector and Foxp3+ Regulatory T Lymphocytes in Myelin Oligodendrocyte Glycoprotein-Induced Experimental Allergic Encephalomyelitis

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 46 publications
(65 reference statements)
3
34
0
Order By: Relevance
“…Classical DNA cloning and Sanger sequencing techniques are laborious and generally limit data to a few hundred, or in rare cases a few thousand, TR sequences per investigation6789. The complexity and depth of the human TR repertoire was recently explored in several studies using next generation sequencing (NGS)121314151617181920. In these studies, Illumina sequencing was primarily used, with a major advantage of generating very deep data, but a disadvantage that the read length was short and the data either required assembly1213 or focused exclusively on the CDR3 (refs 14, 15).…”
mentioning
confidence: 99%
“…Classical DNA cloning and Sanger sequencing techniques are laborious and generally limit data to a few hundred, or in rare cases a few thousand, TR sequences per investigation6789. The complexity and depth of the human TR repertoire was recently explored in several studies using next generation sequencing (NGS)121314151617181920. In these studies, Illumina sequencing was primarily used, with a major advantage of generating very deep data, but a disadvantage that the read length was short and the data either required assembly1213 or focused exclusively on the CDR3 (refs 14, 15).…”
mentioning
confidence: 99%
“…The defined length of 15 amino acids optimized the system for stimulation of CD4 cells (23), and similar approaches in CD8 cells would be complicated by strict peptide length requirements (24). Twenty pools (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were fixed with one of each of the 20 amino acids at position five, another 20 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) at position six, and another 20 (41-60) at position eight. Each of the nonfixed positions was synthesized with a random amino acid.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in mouse models suggest that Treg TCR repertoire breadth and the antigen-specificity of Tregs are important determinants in the suppression of autoimmunity, whereas restricted Treg TCR repertoires, specifically in the context of lymphopenia, can lead to T helper type 2 (Th2)-associated disease (15)(16)(17); however, analogous associations have not been identified in humans. Despite evidence for the intersecting reactivity of Tregs and Teffs, clonotypic analyses repeatedly suggest that even in the context of restricted TCR repertoires, the TCRs of Tregs are largely distinct from effector cells (18)(19)(20)(21)(22), complicating the recognition of abnormalities in regulatory cell specificity. Characterization of such diseases could have implications for treatment and for the role of Tregs in allergy and other forms of immune dysregulation.…”
mentioning
confidence: 99%
“…The Geiger laboratory previously published two studies looking at the hydropathy and charge of CDR3β from Tconv and Treg cells in a myelin oligodendrocyte glycoprotein-specific model (48,49) and found a significant difference only in net charge. In their model, FoxP3 + Treg cells showed a higher charge and seemingly higher hydrophilicity of CDR3β, although the latter was not significantly different because of a much lower number of sequences analyzed than in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This substitution occurred in all three The observed changes in CDR3α amino acid composition clearly indicate that, in the absence of CTLA-4, a shift occurs in the affinity of TCRs of both Tconv and Treg cells. To try and define the difference in binding potential of CDR3α regions, we calculated the isoelectric point (PI; indicative of charge) and average hydrophilicity, which each affect peptide/MHC-binding affinity (48,49). Comparison of the CDR3 properties of the three most common TRAV13.TRAJ combinations in CTLA-4WT Tconv cells with the same combination in matching Treg cells confirmed that Treg cells require different binding characteristics to use the same CDR3α, which was suggested by the change in amino acid composition (Fig.…”
Section: Ctla-4 Affects the Diversity And Sequence Of Endogenous Cdr3αmentioning
confidence: 99%